PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KEJENUHAN BELAJAR SISWA SMP MUHAMMADIYAH BANTUL - Riska Kurniawati Riska; Ulfa Danni Rosada (Dharmas Education Journal (DE_Journal), 2021)
The saturation of student learning is caused by the situation and conditions of the covid-19 pandemic so that learning activities have to be carried out online. During online learning, learning activities are deemed less effective, students cannot interact directly with friends and teachers, learning activities only charge students with assignments, guidance and counseling services are carried out the same every day. This causes students to get bored of learning. This study aims to describe the role of guidance and counseling teachers in overcoming boredom in student learning at SMP Muhammadiyah Bantul. This type of research is descriptive qualitative. The subjects of this study were guidance and counseling teachers and students of grades VII A, VIIA and IX E for the academic year 2021/2022. Data collection techniques in the form of interviews, observation and documentation. Data analysis uses data reduction, data display and drawing conclusions. The results showed that there was learning saturation as indicated by the deviant behavior of students during the covid-19 pandemic. The boredom of learning is overcome by guidance and counseling teachers through the provision of situational guidance and counseling services. Changes in students after being given services can be seen from the increase in learning. Some students said that there was a change after being given the service, while some other students never experienced any change. Steps taken if students do not have changes the teacher will try as much as possible to change students' attitudes through case conferences.